Tapetal Expression of BnaC.MAGL8.a Causes Male Sterility in Arabidopsis - Gao, Jie; Li, Qun; Wang, Nan; Tao, Baolong; Wen, Jing; Yi, Bin; Ma, Chaozhi; Tu, Jinxing; Fu, Tingdong; Li, Qiang; Zou, Jitao; Shen, Jinxiong (Frontiers in Plant Science, 2019)
Monoacylglycerol lipase (MAGL) hydrolyzes monoacylglycerol, producing free fatty acid and glycerol. Although this enzyme has been shown to play important roles in mammal, its potential function in plants remains poorly understood. In a survey of the MAGL genes in Brassica napus, we found tapetal expression of BnaC.MAGL8.a, a homolog of AtMAGL8, results in male sterility in Arabidopsis thaliana. Retarded tapetal PCD and defected pollen wall were observed in the transgenic plants. The tapetal cells became vacuolated at stage 9, and then degenerated at stage 11. Most microspores degenerated with the tapetal cells, and only few pollen grains with an irregular-shaped exine layer were produced in the transgenic plants. Transcriptome analysis identified 398 differentially expressed genes. Most of them are involved in pollen development and stress response. ABORTED MICROSPORES and its downstream pollen wall biosynthesis genes were down-regulated, but genes related with reactive oxygen species homeostasis and jasmonates signalling were up-regulated in the transgenic plants. These results suggest that expression of BnaC.MAGL8.a in tapetum invokes stress response and impairs pollen development. The apparent phenotypic similarity between atgpat1 mutant and BnA9::BnaC.MAGL8.a transgenic plants lead us to propose a role for monoacylglycerol (MAG) in pollen development in Arabidopsis. Our study provides insights on not only the biological function of plant MAGL genes but also the role of MAG in pollen development.